(untitled) (Baghdad Science Journal, 2019)
The aim of this research is to study the surface alteration characteristics and surface morphology of the superhydrophobic/hydrophobic nanocomposite coatings prepared by an electrospinning method to coat various materials such as glass and metal. This is considered as a low cost method of fabrication for polymer solutions of Polystyrene (PS), Polymethylmethacrylate (PMMA) and Silicone Rubber (RTV). Si were prepared in various wt% of composition for each solutions. Contact angle measurement, surface tension, viscosity, roughness tests were calculated for all specimens. SEM showed the morphology of the surfaces after coated. PS and PMMA showed superhydrophobic properties for metal substrate, while Si showed hydrophobic characteristics for both metal and glass substrate. Polymer solution of (15%Si/Thinner (Th)) owned best roughness for glass substrate and polymer solution of (4%PMMA/Tetrahydrofuran (THF)) owned best roughness for metal substrate.